Citizen science in eDNA monitoring for Mediterranean monk seal conservation - Sofia Bonicalza; Elena Valsecchi; Emanuele Coppola; Valeria Catapano; Harriet Thatcher (BMC Ecology and Evolution)
Abstract Background Citizen Science (CS) offers a promising approach to enhance data collection and engage communities in conservation efforts. This study evaluates the use of CS in environmental DNA (eDNA) monitoring for Mediterranean monk seal conservation. We validated CS by assessing the effectiveness of a newly developed CS-friendly filtration system called “WET” (Water eDNA Trap) in eDNA detection, addressing technical challenges, and analysing volunteer faults. The WET is a 4-litre, manual pump-based filtering system using positive pressure to force water through the filter. We also assessed the use of a retrospective questionnaire as a tool to measure CS’s social impact on participants’ perceived knowledge, attitudes, and conservation behaviours. Results Results suggest the WET performs comparably to traditional methods, with minor technical issues. Despite some faults such as not folding or forgetting to change the filter, volunteers were generally reliable in sample processing. Moreover, CS involvement increased participants’ perceived knowledge, affective attitudes, and conservation behaviours towards seal conservation. Volunteers reported a greater understanding of eDNA monitoring, increased interest in monk seal conservation, and more frequent conservation behaviours, including spreading awareness within their community. While these findings are exploratory due to the small sample size (19 participants) and potential ceiling effects in attitude assessment, they provide an initial validation of the questionnaire as a tool for measuring CS’s social outcomes. Future studies with larger sample sizes are needed to confirm these results and investigate their applicability across broader stakeholder groups. Continuous improvement in volunteer training and equipment design is also recommended. Conclusions This study highlights CS’s potential to improve public engagement and knowledge in conservation. By involving diverse participants, CS can play a critical role in long-term conservation efforts and promote sustainable coexistence between humans and monk seals. Furthermore, the validation of the questionnaire offers a valuable framework for evaluating the social impact of CS initiatives in conservation contexts.